KEBIJAKAN PENGADAAN BAHAN PUSTAKA PERPUSTAKAAN AKADEMI KESEHATAN ASIH HUSADA SEMARANG - Moh. Mustofa Hadi (Central Library of Universitas Sebelas Maret, 2019)
This scientific paper discusses one of the development of library collection policy is the procurement of library materials at the Academy of Health Library Asih Husada Semarang. The purpose of this paper is to understand the procurement policy process of library materials at the Academy of Health Library Asih Husada Semarang. The method of procuring library materials at the Academy of Health Library Asih Husada Semarang done through purchases and donations. This paper uses interviews with thelibrary director and field visits directly. The results of the paper indicate that the policy of procurement of library materials has been replicated by the Academy of Health Library of Asih Husada Semarang has been written, but not yet officially formulated, therefore after the procurement process of library materials is completed, evaluated once every year at the end of December through the Foundation Annual Work Meeting.Keywords : collection development, library material procurement policy, procurement method of library materials